Authoritarian Leadership in Universities and Its Impact on Student Enrollment Interest : The Mediating Role of Faculty Performance - Deni Sunaryo; Mukdad Ibrahim; Ahmad Firdaus (Digital Innovation : International Journal of Management, 2025)
The rise of authoritarian leadership in higher education institutions has become a pressing global issue, affecting academic freedom, institutional autonomy, and the wellbeing of faculty and students. This phenomenon, observed not only in traditionally authoritarian countries but also in democratic contexts, manifests through centralized power, top-down decision-making, and suppression of critical voices. Despite its growing prevalence, empirical research on authoritarian leadership in academia remains limited, with significant gaps in understanding its contextual dynamics, direct impacts on academic communities, and cross-cultural variations. Recent studies have introduced novel theoretical frameworks tailored to academic settings and employed innovative mixed-method approaches to explore mediating factors such as emotional exhaustion and moderating personality traits. These advances have highlighted the complex and contextual nature of authoritarian leadership’s effects, which generally undermine innovation, morale, and performance, although it may increase compliance in specific situations. The negative consequences of authoritarian leadership are evident in reduced creativity and critical thinking, which are fundamental to the academic mission. Faculty members and students may experience heightened stress, diminished job satisfaction, and a decline in engagement. However, some studies suggest that in certain environments, authoritarian leadership can impose order and enhance efficiency in situations requiring immediate decisions. This paper underscores the urgent need for further research and practical interventions to promote adaptive, collaborative, and wellbeing-oriented leadership models in higher education. Such leadership approaches are essential to foster institutional resilience, democratic governance, and inclusive educational practices in an era of global uncertainty and disruption. By shifting towards more participatory leadership styles, higher education institutions can better address the evolving needs of faculty and students, ensuring a thriving academic environment that supports innovation, diversity of thought, and overall wellbeing.